PENGARUH MOTIVASI, DISIPLIN DAN KOMITMEN PEGAWAI TERHADAP PRESTASI KERJA PEGAWAI PADA PT. JASA RAHARJA (PERSERO) CABANG BANGKA BELITUNG - Teguh Afrianto; Chandra Suwondo; Wargianto . (LPPM STIE PERTIBA Pangkalpinang, 2017)
The purpose of research is to analyze the influence of motivation, discipline and employee commitment to employee performance at PT. Jasa Raharja (PERSERO) Bangka Belitung Branch. The research method used survey method. Research respondents are all employees of PT. Jasa Raharja (PERSERO) Bangka Belitung Branch of 32 people. Variables used are job performance, motivation, discipline and employee commitment. This research uses quantitative analysis. The data of this research is primary research result directly in the field. The research data is analyzed by regression analysis technique which is done by SPSS software version 17.The results of this study are 1) There is a positive and significant influence of motivation variable on employee performance at PT Jasa Raharja (Persero) Bangka Belitung Branch. 2) There is a positive and significant influence of the discipline variable on the performance of employees at PT Jasa Raharja (Persero) Bangka Belitung Branch. There is a positive and significant influence of employee commitment variable to employee performance at PT Jasa Raharja (Persero) Bangka Belitung Branch 4) There are a positive influence and significant variable of motivation, discipline, and employee commitment together towards employee performance at PT Jasa Raharja (Persero ) Bangka Belitung Branch.